Secure Consensus of Nonlinear Multi-Agent Systems Under Limited Communication Bandwidth and DoS Attacks - Wang, Xinhe (2023 International Conference on Neuromorphic Computing (ICNC), 2023)
In this paper, secure consensus of uncertain nonlinear multi-agent systems is studied under the constrains of limited bandwidth and denial-of-service (DoS) attacks. A double-loop controller is proposed, where a sampling-based encoding-decoding scheme is considered in outer-loop controller to handle the limited bandwidth of communication channel, and sliding model control approach and neuro-adaptive law are designed in inner-loop to deal with the uncertainty of nonlinear systems. Secure consensus is achieved under the control strategy when DoS attacks are subject to mild constrains in the form of frequency and duration. Simulations are given to verify the effectiveness of the control strategy.